Pengaruh Komposisi Nanosilika Terhadap Kinerja Mekanik Aspal Hibrida Berbasis Mikroorganisme - Muhamad Khalid Khadafi; Ratnawulan Ratnawulan; Riri Jonuarti; Syafri Syafri (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The decline in pavement performance due to increasing traffic loads necessitates the development of advanced materials beyond conventional asphalt mixtures. This study investigates the effect of nanosilica composition on the mechanical performance of hybrid Asphalt Concrete-Wearing Course (AC-WC) modified with Escherichia coli as a biomineralization agent. The mixture was prepared using a fixed asphalt content of 6% and nanosilica variations of 0%, 3%, 5%, and 9% by asphalt weight, combined with bacterial concentration of 10³ cells/mL. Marshall testing was conducted in accordance with Bina Marga 2018 Revision 2 specifications. The results indicate that nanosilica addition leads to a gradual decrease in density from 2.472 to 2.453 g/cm³, while significantly increasing stability from 1,094 kg to 1,560 kg. Flow values ranged between 3.90 and 4.20 mm, with higher compositions exceeding specification limits. The 5% nanosilica composition demonstrated the most balanced performance across all parameters. The synergistic interaction between nanosilica and bacterial activity enhances interparticle bonding, offering a promising approach for developing durable and sustainable asphalt materials.